Tp53. Tp053 Sepsis and Multiorgan Failure 2021
DOI: 10.1164/ajrccm-conference.2021.203.1_meetingabstracts.a2726
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Resuscitation in Sepsis by Different Weight Calculations and In-Hospital Mortality

Abstract: Obese patients receive less volume by body weight compared to normal weight classes in shock models yet have improved mortality outcomes. We describe the variation in volume and vasopressor resuscitation in septic shock by BMI (Body Mass Index). We aim to determine the optimal weight: actual, adjusted and ideal to calculate 30ml/kg fluid administration in sepsis resuscitation in association with in-hospital mortality. Methods: We included septic shock patients from VOLUME-CHASERS cohort between September 2017 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Given MV's hypotension, the ED NP was correct in prescribing the rest of the bolus, which subsequently was given within 3 hours of recognition. With a body mass index over 30, it is acceptable to prescribe crystalloids based on ideal body weight, and studies to date have not shown any significant difference in mortality in patients who receive an adjusted fluid bolus 35-38. However, the selection of crystalloid did not reflect the updated guidelines 1.…”
Section: Discussion and Follow-upmentioning
confidence: 99%
See 1 more Smart Citation
“…Given MV's hypotension, the ED NP was correct in prescribing the rest of the bolus, which subsequently was given within 3 hours of recognition. With a body mass index over 30, it is acceptable to prescribe crystalloids based on ideal body weight, and studies to date have not shown any significant difference in mortality in patients who receive an adjusted fluid bolus 35-38. However, the selection of crystalloid did not reflect the updated guidelines 1.…”
Section: Discussion and Follow-upmentioning
confidence: 99%
“…With a body mass index over 30, it is acceptable to prescribe crystalloids based on ideal body weight, and studies to date have not shown any signifi cant difference in mortality in patients who receive an adjusted fl uid bolus. [35][36][37][38] However, the selection of crystalloid did not refl ect the updated guidelines. 1 Rather, the ED NP prescribed 0.9% sodium chloride solution, which echoed the hospital culture norms.…”
Section: ■ Clinical Vignette MV Is a 52-year-old Male Who Is Unemploy...mentioning
confidence: 99%